Analisis Kriminologi Perilaku Seks Menyimpang Warga Binaan Lembaga Pemasyarakatan di Provinsi Gorontalo - Martvina Sapii; Sumiyati Beddu; Rafika Nur (Pusat Riset dan Inovasi Nasional, 2023)
This research focuses on implementation, benefits, and to find out the problems faced in the treatment of inmates with deviant sexual behavior. This study raises the issue of how legal protection is given to victims of inmates with deviant sexual behavior in Class IIA Gorontalo Correctional Institutions and what are the obstacles faced by correctional officers in providing legal protection to victims of inmates with deviant sexual behavior. This study used interview and observation research methods, which described the treatment of inmates with deviant sexual behavior, then analyzed and concluded using a qualitative approach. Based on the analysis, it was found that the treatment of inmates with deviant sexual behavior was considered very necessary. Inmates with deviant sexual behavior have characteristics that are unique and different from other inmates in general. In general, inmates with deviant sexual behavior scattered in prisons throughout Indonesia are men who look like women or who like the same sex. Inmates with deviant sexual behavior are very vulnerable to bad treatment by other inmates, and can also have a negative influence on other inmates. Special treatment for inmates with deviant sexual behavior is deemed necessary, starting from placement in individual blocks to special coaching. There are obstacles encountered in its implementation, including the procurement of individual blocks of inmates with deviant sexual behavior and the understanding of Correctional Officers about the problems and deviations that will be caused by the presence of inmates with deviant sexual behavior in correctional institutions.